Diameters of Perikarya in Different Regions of Rat Central Nervous System after Streptomycin and Kanamycin Intoxication - Rati Tandon; Prerna Gupta; Masooma Syed; Nafis Ahmad Faruqi (Academia Anatomica International, 2019)
Introduction: Streptomycin and Kanamycin, an aminoglycosidic antibiotic, is known to destroy the ventral cochlear nuclei of brainstem in man. Ototoxicity is well known side effect of kanamycin, the effect on central nervous system in general and central auditory pathway in particular is still unclear. Subjects and Methods: Thirty albino rats were divided into three groups I, II and III of ten animals each. Group III was control. Group I and II received Streptomycin (30mg/Kg body weight) and kanamycin (400mg/kg body weight) intramuscular injections, daily for 3 weeks. Paraffin embedded sections of cerebellum, spinal cord, dorsal cochlear nucleus, inferior colliculus nucleus and auditory cortex were stained with haematoxylin and eosin stains and perikarya measured using slide and ocular micrometres. Results: Size of cerebellar Purkinje cells increased significantly in control rats for streptomycin and kanamycin intoxicated animals respectively. Ventral horn cells of spinal cord are affected highly significantly only by streptomycin. Vestibular nucleus also showed similar results i.e. neuronal body. Neurons of dorsal cochlear nucleus is affected significantly by both the drugs i.e. streptomycin and kanamycin. Conclusion: Streptomycin causes an increase in diameter of auditory cortical cells on other hand kanamycin led to highly significant decrement in size of cells of same region. Preferential affinity and differential effects were noticed. The latter throws some clues about mechanism of action.